2020
DOI: 10.1089/jpm.2019.0632
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Nonpharmacological Intervention to Prevent Delirium for Hospitalized People with Advanced Cancer: A Phase II Cluster Randomized Waitlist Controlled Trial (The PRESERVE Pilot Study)

Abstract: Number of tables: 3 Number of figures: 3 Number of references: 38 Word count: 2936 Background Delirium is a common debilitating complication of advanced cancer. ObjectiveTo determine if a multicomponent non-pharmacological delirium prevention intervention was feasible for adult patients with advanced cancer, prior to a phase III (efficacy) trial. DesignPhase II (feasibility) cluster randomized controlled trial. All sites implemented delirium screening and diagnostic assessment. Strategies within sleep, vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 36 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…In view of the lack of evidence to support the routine use of medication for delirium symptoms, an increased focus is needed on non-pharmacological approaches to care, including prevention. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the lack of evidence to support the routine use of medication for delirium symptoms, an increased focus is needed on non-pharmacological approaches to care, including prevention. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In view of the lack of evidence to support the routine use of medication for delirium symptoms, an increased focus is needed on non-pharmacological approaches to care, including prevention. 10 The WHO definition identifies family as important recipients of palliative care, as well as the patient. 34 The included studies demonstrated that clinicians went beyond 'person-centred' care of the patient, in responding to the distress and needs of the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors declare that there is no conflict of interest. 22,23,25 Open label RCT 24,26 Clustered RCT 27 26 Single blind RCT 29 Historical control study 30 Before and after study 31 Non-randomised study Palliative care unit or inpatient hospice 25,27,28,30,31 Hospital palliative care 24,[32][33][34] Palliative care unit/hospice and hospital 23,26,29 Community palliative care 22…”
Section: Declaration Of Conflict Of Interestmentioning
confidence: 99%
“…Direct care [22][23][24][25][26][27][28][29][30][31]34 11 Not reported 32,33 Disciplines involved in service Medical and nursing…”
Section: Palliative Service Modelmentioning
confidence: 99%